Gender equality and protection for the girl-child education in conflict environments: The case of Afghanistan and Nigeria - Oluwashakin, Ajinde (Journal of Contemporary International Relations and Diplomacy, 2022)
Certain cultural practices and poverty have inhibited girls’ and women’s life chances and opportunities for long before the dawn of the 21st century, regardless of their number and productivity. Moreover, in most developing countries, girl-child education has not been given the priority it deserved. While the gender equality issue has gained global attention at the level of the United Nations since 1948, it is still regarded as ‘unfinished business,’ of our time. Therefore, the paper examines the vulnerability facing girl-child education and the protection needed to secure their education, for their self-dignity and sustainable development. The feminist theory is adopted, as well as the concept of the responsibility to protect (R2P). The study is descriptive and utilizes data from books, journals, newspapers, and websites of relevant organizations, especially the UN, UNESCO, and UNICEF. Content analysis of daily news feeds, from verified media stables, provides authentic data. Findings revealed that the girl-child is more vulnerable than the boy-child in conflict environments. There is a deliberate assault on girl-child education. More girls are out-of-school than boys. Both the domestic and foreign policies of the Nigerian and Afghan governments clearly showed the extent of their responsibility to protect girl-child education, partly to achieve the UN and AU quality education goal. The paper concludes that the protection of girl-child education must be made a priority of the state because the female gender is the bearer of life and reproductive sustainability. The girl-child should be provided with free quality education to be equipped for economic empowerment. School premises in conflict environments need to be more fortified from terrorists, bandits, and kidnappers. Intelligence gatherings need to be broadened and sustained such that government security agencies should not only be on the defensive but also the offensive against terrorist operational bases.